2021
DOI: 10.1002/jgm.3309
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA SNHG8 promotes prostate cancer progression through repressing miR‐384 and up‐regulating HOXB7

Abstract: Background Multiple long non‐coding RNAs (lncRNAs) have been demonstrated to function as vital regulators in the progression of prostate cancer (PCa). In the present study, we aimed to probe the function of lncRNA small nucleolar RNA host gene 8 (SNHG8) in PCa progression. Methods A quantitative real‐time polymerase chain reaction and western blotting were utilized to measure SNHG8, microRNA‐384 (miR‐384) and homeobox B7 (HOXB7) expression. Call‐couting kit‐8 and bromodeoxyuridine experiments were employed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The dysregulated lncRNAs probably modulate tumorigenesis and other biological functions (28)(29)(30). Our result is consistent with others' reports that SNHG8 is associated with the progression in multiple types of cancer in the liver, colon, lung, ovary, prostate, esophagus, and so on (15,(31)(32)(33)(34)(35). Our data support that the acting mechanism of SNHG8 could be multiple: (1) it activated BCL-2, preventing GC cells from apoptosis; (2) it activated CCND1, regulating the cell cycle; and (3) it activated CDH1, CDH2Snai1, and VIM, enhancing the epithelial-mesenchymal transition, thus promoting the migration, invasion, and metastasis of GC cells.…”
Section: Discussionsupporting
confidence: 92%
“…The dysregulated lncRNAs probably modulate tumorigenesis and other biological functions (28)(29)(30). Our result is consistent with others' reports that SNHG8 is associated with the progression in multiple types of cancer in the liver, colon, lung, ovary, prostate, esophagus, and so on (15,(31)(32)(33)(34)(35). Our data support that the acting mechanism of SNHG8 could be multiple: (1) it activated BCL-2, preventing GC cells from apoptosis; (2) it activated CCND1, regulating the cell cycle; and (3) it activated CDH1, CDH2Snai1, and VIM, enhancing the epithelial-mesenchymal transition, thus promoting the migration, invasion, and metastasis of GC cells.…”
Section: Discussionsupporting
confidence: 92%
“…Accumulating studies have shown that lncRNAs exert their biological roles by acting as miRNA sponges [ 30 , 31 ]. For example, lncRNA SNHG8 is reported to contribute to the development of prostate cancer by elevating HOXB7 expression via sponging miR-384 [ 32 ]. lncRNA MCM3AP-AS1 is reported to restrain the development of colorectal cancer through mediating miR-19a-3p/FOXF2 signaling [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…35 Small Nucleolar RNA Host Gene 8 (SNHG8) can promote the proliferation and migration of multiple tumor cells through serving as sponge for different miRNAs. [36][37][38] Our results revealed that the ARHGAP22-IT1 and SNHG8 were overexpressed in TAD patients. According to the ceRNA hypothesis, the ARHGAP22-IT1 and SNHG8 can competitively bind to hsa-miR-3202 and upregulate SLC7A5, thus promoting VSMC proliferation and TAD development.…”
Section: Discussionmentioning
confidence: 57%